A Bibliometric Analysis of Research Trends, Themes and Collaborations in Skin Whitening Studies Using Scopus Data - Lindsay Valerie Andres; Rheajoy A. Enriquez; Deine Westlee R. Gulmatico; Kirk Kenzo M. Tongcua; Jennifer P. Solis (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Skin whitening has become a significant area of research in cosmetics science and dermatology due to the increasing global demand for products that reduce skin pigmentation and improve skin appearance. This study presents a bibliometric analysis of skin whitening research published between 2021 and 2024 using 175 documents retrieved from the Scopus database. Bibliometric analyses and network visualization were performed using Biblioshiny in R, while Microsoft Excel for data cleaning. The study examined publication trends, leading countries and institutions, citation performance, collaboration networks, and thematic evolution of research in the field. The findings revealed that China, South Korea, and the United States were the most productive contributors, while the Journal of Cosmetics Dermatology and the International Journal of Molecular Sciences emerged as the leading publication sources. Thematic analysis showed that research has progressively shifted from traditional depigmentation agents and clinical dermatology toward molecular mechanisms, skin pigmentation pathways, therapeutic innovations, and advanced cosmetic formulations. Increasing International collaboration and interdisciplinary research further indicate the growing scientific interest in skin whitening studies. These findings provide a comprehensive overview of the current knowledge structure and emerging research directions in skin whitening research, offering valuable insight for researchers, dermatologists, cosmetic scientists, and policymakers in guiding future investigations, product development and evidence-based public health and regulatory initiatives.